Share (DPS) Terhadap Harga Saham Perusahaan Yang Terdaftar Dalam Indeks LQ45 Di Bursa Efek Indonesia (BEI) Periode Tahun 2018 – 2022 - Siti Mi'Danur Rahmah; Jojok Dwiridotjahjono (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Financial reports are crucial information for investors in evaluating a company's performance. Investment decisions often rely on information from financial reports and stock prices. This research aims to examine the impact of variables such as EPS, PER, DER, ROE, and DPS on the stock prices of companies listed on the LQ45 index during the period 2018-2022. The research method utilizes multiple linear regression analysis with a sample of 16 companies. The results indicate that all five variables collectively have a significant impact on stock prices. Specifically, EPS and PER have a positive and significant influence, DER has a positive but nonsignificant influence, while ROE and DPS have a positive and significant impact. Despite some variables being nonsignificant, these findings can aid in making more contextual investment decisions in the Indonesian stock market.